PENGARUH PENAMBAHAN TEPUNG BUAH MANGROV PEDADA (Sonneratia caseolaris) PADA MUTU DODOL KETAN - Nurfadilah Nurfadilah (Jurnal Pengolahan Pangan, 2019)
Mangroves are plants that live on the shores of the coast with various types of mangroves, but the mangroves used in the study are pedada, European communities know him with designation Sonneratia caseolaris . Mangrove ecosystems have benefits economical that is results wood and notwood for example brackish water cultivation, ponds shrimp, tour a and others. Benefits ecological is in the form of protection for the ecosystem mainlandand the ocean, that is could to be anchoring abrasion or erosion wave or wind tight. Mangroves have value economical important because have rightdungan high arbohydrates. Research this aiming for knowing level substitution flour sticky rice and which produces mangrove mangrove flour dodol with organoleptic high quality . This study used a Randomized Block Design (RBD) with 5 treatments. From the results whole test organoleptic above assessed by penelis from level fondness color, aroma, taste, texture, and fondness whole showing that penelis more like level 10% substitution with use 20 grams of mangrove flour and 180 grams of flour sticky rice.